Heat and mass transfer of Dioscorea opposita Thunb. cv. Tiegun slices during hot⁃air drying process - PANG Lingyun; YUAN Zhihua; ZHAN Lijuan; LI Yu; PAN Siyi (Shipin yu jixie)
ObjectiveThis study aimed to investigate the mass transfer of Dioscorea opposita Thunb. cv. Tiegun slices, the heat transfer of the drying space and yam slices. during hot⁃air drying (HAD) process.MethodsSeven thin⁃layer drying models were used to fit the drying curves of yam slices during the HAD process, and the optimal mass transfer dynamics model was selected finally. Thermal conductivity and specific heat capacity of yam slices were measured at different temperatures. ANSYS software was used to simulate the temperature field changes in the drying chamber and the temperature changes of yam slices.ResultsThe Modified Page model can accurately predict the moisture changes of yam slices during the HAD process at different temperatures (R2=0.998 96~0.999 86). For HAD, the temperature inside the drying chamber was generally high near the air inlet and outlet on the horizontal plane, and was slightly low in the distance. Differently, the temperature decreased mildly from the top to the bottom vertically. During HAD, the temperature of yam slices was the lowest in the center and highest at the outer surface. The temperature difference between the inner and outer layers gradually decreased, and the temperature changed faster in the early stage than in the late stage. The maximum temperature difference between the measured value and the simulated value was 7.75 ℃, and the minimum was only 0.07 ℃, indicating that the simulation results were reliable.ConclusionThe Modified Page model and ANSYS software can accurately predict the heat and mass transfer of yam slices during the HAD process.